STRUCTURAL-SEMANTIC SIMILARITIES AND DIFFERENCES IN THE SPHERE OF COLOR DESIGNATIONS - Tashlanova Nigora Djuraevna (Bright Mind Publishing, 2025)
This article reveals a comparative study of the vocabulary of color naming, the totality of knowledge about the world, reflected in vocabulary, grammar, phraseology, as an idea of reality, reflected in linguistic signs and their meanings, and hypotheses were put forward about the relationship between the number of color designations with the level of cultural development of society.